The Impact of Effective Vaccination on Clinical and Radiological Involvement in COVID-19 Patients - Coskun DOGAN; Deniz BILICI; Burcu ARPINAR YIGITBAS; Omer ZENGIN; Orhan ZOR; Oguzhan AKMAN; Ilyas KOCABAG; Gonul Seven YALCIN; Esra ERTAN YAZAR (Medeniyet Medical Journal)
Objective: We aimed to analyze clinical, radiological, and laboratory differences between vaccinated and unvaccinated patients admitted to hospital due to coronavirus disease-2019 (COVID-19) pneumonia. Methods: Patients hospitalized in the COVID-19 clinic between February 2022 and August 2022 were included in the study. Demographic, clinical features, and treatment results. Furthermore, the COVID-19 vaccination status of the cases was recorded. The cases were divided into two groups as those with and without COVID vaccination and compared. Results: A total of 215 patients were included in our study, and the patients were divided into 2 groups according to their vaccination status: those who were unvaccinated against COVID-19 (n=100) and those who vaccinated COVID-19 (n=115). The presence of comorbid chronic diseases and cancer was lower in the unvaccinated group. The duration of hospitalization was longer in the unvaccinated group than in the vaccinated group (9.6 and 7.1 days, respectively) (p<0.001). While there was no difference between the two groups in terms of the radiological involvement pattern, the number of involved segments was significantly higher in the unvaccinated group (p<0.05). The number of patients who received high-dose glucocorticoid therapy in the unvaccinated group was higher (28 cases vs. 11 cases; p<0.001). There was no statistically significant difference between the two groups in terms of transfer of patients to the intensive care unit (p>0.05). 11.3% (13/115) of the patients in the vaccinated group died, whereas 14% (14/100) died in the unvaccinated group. Conclusions: The vaccinated cases who were infected with COVID-19 had a shorter duration of hospitalization and lower severity of radiological involvement. The requirement for pulse steroids was also less compared with unvaccinated individuals. Despite having chronic diseases and cancer, which is considered to have a significant effect on mortality in COVID-19 patients. In addition, although the vaccinated group was older, they had mortality rates similar to those of unvaccinated subjects.